STUDY TO DETERMINE AWARENESS AND ACCEPTANCE OF FAMILY PLANNING PRACTICES AMONG THE TRIBAL POPULATION OF JHARKHAND- A CROSS-SECTIONAL STUDY. - Indrani Dutta; Atima Bharti (Student's Journal of Health Research, 2023)
Objective: The reduction in potency and inter-birth interval can decrease the chances of newborn and maternal death. With the execution of the national fertility program, there is a reduction in fertility rates considerably, but it persists in endemic groups in rural parts of India. This study was conducted to evaluate the knowledge of contraception and practice by type in tribal women in Jharkhand. Methods and Materials: This is a cross-sectional study carried out in a tribal area of Jharkhand. In this study, 200 pregnant women were included. With the observation of a single characteristic complex analyses were conducted to know the number and characteristics of people living in this area and behavioural factors related to the understanding of contraceptive methods. Results: All the tribal women were well acquainted with female sterilization. Few of the women around 40% knew about temporary contraception and 35% of the women did not know where to get them. The majority of the women knew about copper T (34%), but only 29.1% had knowledge of oral contraceptives and condoms (12%). Temporary contraception was utilized by 3% of the women. Conclusion: This study evaluated less or no awareness and usage of temporary contraceptive methods among tribal people in Jharkhand. The main aim is to make them aware of the different contraceptive methods for inter-birth intervals and should focus on young women. Recommendation: Awareness of various methods of contraception needs to be mass introduced to people in tribal regions. Therefore, this research shows the requirement for complete education and encouragement related to temporary methods of contraception in tribal women.